Effect of pH on the Electrochemical Behavior of Hydrogen Peroxide in the Presence of Pseudomonas aeruginosa - Espinoza-Vergara, Javier; Molina, Paulo; Walter, Mariana; Gulppi, Miguel; Vejar, Nelson; Melo, Francisco; Urzua, Marcela; Muñoz, Hugo; Zagal, José H.; Zhou, Xiaorong; Azocar, Manuel I.; Paez, Maritza A. (Frontiers in Bioengineering and Biotechnology, 2021)
The influence of pH on the enzymatic activity of catalase produced by Pseudomonas aeruginosa was investigated using electrochemical techniques. Cyclic and square wave voltammetry were used to monitor the enzymatic activity. A modified cobalt phthalocyanine (CoPc) carbon electrode (OPG), a known catalyst for reducing O2 to H2O2, was used to detect species resulting from the enzyme activity. The electrolyte was a sterilized aqueous medium containing Mueller-Hinton (MH) broth. The open-circuit potential (OCP) of the Pseudomonas aeruginosa culture in MH decreased rapidly with time, reaching a stable state after 4 hours. Peculiarities in the E / I response were observed in voltammograms conducted in less than 4 hours of exposure to the culture medium. Such particular E/I responses are due to the catalase's enzymatic action related to the conversion of hydrogen peroxide to oxygen, confirming the authors' previous findings related to the behavior of other catalase-positive microorganisms. The enzymatic activity exhibits maximum activity at pH 7.5, assessed by the potential at which oxygen is reduced to hydrogen peroxide. At higher or lower pHs, the oxygen reduction reaction (ORR) occurs at higher overpotentials, i.e., at more negative potentials. In addition, and to assess the influence of bacterial adhesion on the electrochemical behavior, measurements of the bacterial-substrate metal interaction were performed at different pH using atomic force microscopy.